Correction: Tyrosine bioconjugation – an emergent alternative. Issue 43 (31st October 2022) - Szijj, Peter A.; Kostadinova, Kristina A.; Spears, Richard J.; Chudasama, Vijay
Abstract : Correction for 'Tyrosine bioconjugation – an emergent alternative' by Peter A. Szijj et al., Org. Biomol. Chem., 2020, 18, 9018–9028, ; https://doi.org/10.1039/D0OB01912G .